PENGARUH DISIPLIN, MOTIVASI DAN STRESS KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA DINAS KOMUNIKASI DAN INFORMATIKA PROVINSI SUMATERA UTARA - Efry Kurnia; Roza Maya Sari (Jurnal Ilmiah Global Education, 2023)
This study aims to analyze the influence of Discipline, Motivation and Work Stress on the Performance of Civil Servants at the Information Communication Service of North Sumatra Province. This study uses a quantitative research approach with a census survey method, namely using the entire population as a sample of 77 people and using a questionnaire as the main data collection tool. Data analysis in this study used multiple linear regression analysis method. The results of the regression analysis show that the discipline variable has a positive value with a significant influence on employee performance, the motivational variable has a positive value with a significant effect on employee performance, the work stress variable has a negative value and a significant effect on the performance of civil servants at the Informatics Communications Office of North Sumatra Province . Meanwhile, simultaneously the variables of discipline, motivation and work stress have a significant effect on the performance of civil servants at the Informatics Communications Office of North Sumatra Province